2010
DOI: 10.1021/je100715x
|View full text |Cite
|
Sign up to set email alerts
|

Densities, Viscosities, and Refractive Indices of Binary Mixtures of Diethyl Oxalate with Some Ketones at (303.15, 308.15, and 313.15) K

Abstract: Densities, viscosities, and refractive indices of binary liquid mixtures of diethyl oxalate (DEO) with four ketones (acetophenone, cyclopentanone, cyclohexanone, and 3-pentanone) were determined over the complete concentration range at (303.15, 308.15, and 313.15) K. The experimental values of mixtures and pure liquids have been used to calculate the excess molar volumes, deviations in viscosity, and deviations in molar refractions. These excess or deviation properties were fitted to the Redlich-Kister type eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…In the liquid state these polar compounds are widely used as relatively safety solvents. In the solid state, due to the globular shape of the molecules, cycloalkanones form one or more orientational disordered phases, also known as rotor or plastic phases. The physicochemical properties of cycloalkanones are the subject of numerous studies, ,, but a literature survey reveals only a few studies on the dielectric properties of the compounds. In general, the studies were not systematic. In this paper we present the results of systematic experimental studies which discovered a very peculiar behavior of the static dielectric permittivity of cycloalkanones in relation to the size of the rings of these compounds.…”
Section: Introductionmentioning
confidence: 99%
“…In the liquid state these polar compounds are widely used as relatively safety solvents. In the solid state, due to the globular shape of the molecules, cycloalkanones form one or more orientational disordered phases, also known as rotor or plastic phases. The physicochemical properties of cycloalkanones are the subject of numerous studies, ,, but a literature survey reveals only a few studies on the dielectric properties of the compounds. In general, the studies were not systematic. In this paper we present the results of systematic experimental studies which discovered a very peculiar behavior of the static dielectric permittivity of cycloalkanones in relation to the size of the rings of these compounds.…”
Section: Introductionmentioning
confidence: 99%
“…In view of the above salient features an attempt has been made to elucidate molecular interaction studies in binary liquid mixtures of ketones with n -butyl acetate. A literature survey showed that there exist very limited reports on thermodynamic and transport properties for binary mixtures of ketones with various organic solvents. Likewise, there are some reports on binary mixtures of n -butyl acetate with different organic solvents. In continuation of our earlier work, , we report densities and viscosities for binary systems of n -butyl acetate with acetophenone, cyclopentanone, cyclohexanone, or 3-pentanone at the temperatures of (298.15, 303.15, 308.15, and 313.15) K and atmospheric pressure over the entire composition range. The experimental data are used to calculate excess molar volume V E and excess free energy of activation of viscous flow Δ G * E of the mixtures.…”
Section: Introductionmentioning
confidence: 76%
“…1−7 Likewise, there are some reports on binary mixtures of n-butyl acetate with different organic solvents. 8−11 In continuation of our earlier work, 12,13 we report densities and viscosities for binary systems of n-butyl acetate with acetophenone, cyclopentanone, cyclohexanone, or 3pentanone at the temperatures of (298. 15, 303.15, 308.15, and 313.15) K and atmospheric pressure over the entire composition range.…”
Section: ■ Introductionmentioning
confidence: 86%
“…The free volumes increase with the increase of cyclohexane and its derivative concentration binary liquid mixtures, whereas in the case of cyclohexanone + decan-1-ol the free volume decreases in the higher mole fraction region. The relation of entropy rises and rearrangement of solvate structures especially in high concentration range is indicated by variation of slope of isotherm. , …”
Section: Resultsmentioning
confidence: 99%
“…The relations of mole fraction with b / V and V f / V for the investigated systems are shown in Figures and , respectively. The structural change/rearrangement of solvates has been suggested by the shape change of the curves in the high concentration range. , At higher concentrations, regions of cyclohexane and its derivatives were reflected by the differences in the packing efficiency. The order of space filling ability of different systems in the dense concentration region of cyclohexane and its derivatives are as space-filling ability cyclohexane+1‑decanol < space-filling ability cyclohexanone+1‑decanol/cyclohexyl amine+1‑decanol .…”
Section: Resultsmentioning
confidence: 99%